CORRRELATION BETWEEN STUDENTS‟ GRAMMAR MASTERY AND THEIR ABILITY IN WRITING SPOOF TEXT AT THE FIRST SEMESTER OF THE ELEVENTH CLASS OF MA MA‟ARIF KATIBUNG LAMPUNG SELATAN 2015/2016 - Zwesty, Ermina Deasya (LPPM STKIP PGRI Bandar Lampung, 2016)
Writing is a way to express idea, thinking, feeling, that are arrange from the words into sentence in written form. Writing spoof text is involved into one of these skills that have to be mastered by the students. Writing spoof text is also involved in the curriculum of Indonesia Education for senior high school. But one important thing that has to be concerned in writing spoof is the grammar. So, the result of writing will be better if we can use the correct grammar, because the measure of grammar can cause misunderstanding. From this case, the writer wants to discuss their writing ability by mastering grammar. The objectives of this research is to know the correlation between students‟ grammar mastery and their ability in writing spoof text. The method of this research was descriptive quantitative method. The population of this research was 72 students which consisted of eleventh classes. The sample of the research was 36 students. The sampling technique was stratified random sampling technique. In data collecting technique was multiple choice for grammar mastery and essay test for writing ability. In analyzing the data the writer used multiple correlation formula. Based on the calculation in Chapter IV, it can be seen that rcount is 0.717. It means that rcount is more than 0.00. So there is possitive correlation or there is correlation between students‟ grammar mastery and their ability in writing spoof text.